2021
DOI: 10.1021/acs.jpcc.0c11422
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Core Halogenation on the Electronic Structure of Naphthothiadiazole Derivatives

Abstract: Naphthothiadiazoles are promising electron acceptors for applications in organic semiconductor-based (opto)­electronic devices. Here, we studied the structural and electronic properties of naphthothiadiazole (NTD) derivatives adsorbed on Au(111) in the monolayer and thin films using temperature-programmed desorption as well as vibrational and electronic high-resolution electron energy loss spectroscopy. In addition, we performed state-of-the-art quantum chemical calculations to further illuminate electronic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…15–28 High-resolution electron energy loss spectroscopy (HREELS) provides the required insight into both adsorption and electronic properties of molecular compounds at interfaces to (semi)conducting surfaces and within thin films. 11,29–39 Depending on the primary energy of the incident electrons molecular vibrations or electronic transitions can be excited, including optically forbidden transitions (singlet to triplet states) as already successfully demonstrated for some organic compounds 40–42 including also the N-heteropolycycle 6,13-diazapentacene (6,13-DAP). 12 While the adsorption and electronic properties of pentacene (PEN) and its derivatives adsorbed on various metallic substrates have been investigated in great detail (see for example ref.…”
Section: Introductionmentioning
confidence: 99%
“…15–28 High-resolution electron energy loss spectroscopy (HREELS) provides the required insight into both adsorption and electronic properties of molecular compounds at interfaces to (semi)conducting surfaces and within thin films. 11,29–39 Depending on the primary energy of the incident electrons molecular vibrations or electronic transitions can be excited, including optically forbidden transitions (singlet to triplet states) as already successfully demonstrated for some organic compounds 40–42 including also the N-heteropolycycle 6,13-diazapentacene (6,13-DAP). 12 While the adsorption and electronic properties of pentacene (PEN) and its derivatives adsorbed on various metallic substrates have been investigated in great detail (see for example ref.…”
Section: Introductionmentioning
confidence: 99%
“…Previous measurements of aromatic Nheteropolycycles have clearly demonstrated that at this coverages the molecules are electronically decoupled from the metallic substrate. [31][32][33]40,43,44 In the HREEL spectrum several electronic transitions are clearly detectable at 3.4, 3.5, 3.85, 3.95, 4.5, and 5.4 eV including also vibrational contributions. The peaks at 3.4 and 3.5 eV in the HREEL spectrum, are the 0−0 and 0−1 vibrational transitions of the S 0 → S 0 excited state, with vibrational contributions of the out-of-plane γ ω (C−N−C) and γ ω (C−H) vibrations with frequencies of about 754 cm −1 (93 meV).…”
Section: ■ Methodsmentioning
confidence: 99%
“… 17 The latter can be determined in surface-adsorbed molecules with 2PPE, 10 13 , 18 differential reflectance spectroscopy, 19 22 or high-resolution electron energy loss spectroscopy. 18 , 23 29 …”
Section: Introductionmentioning
confidence: 99%
“…), which is different from the optical gap (highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) transition leading to exciton formation) . The latter can be determined in surface-adsorbed molecules with 2PPE, , differential reflectance spectroscopy, or high-resolution electron energy loss spectroscopy. , …”
Section: Introductionmentioning
confidence: 99%